STUDY OF SUSPENDED SEDIMENT IN THE ESTUARY OF MENDOL ISLAND OF KAMPAR SUBDISTRICT OF PELALAWAN RIAU - Rahmadona, Fitri; Ghalib, Musrifin; ', Mubarak (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACK The research was conducted in May 2014 and took place in Mendol Island estuary of Kampar Subdistrict of Pelalawan Regency. Theanalysis were conducted in the Laboratory of Ecology of the Faculty of Fisheries and Marine Science, University of Riau. The study aims to determine distribution of suspended sediment and factors that influence the distribution of suspended solids. The method used was a survey method, the samples were analyzed by using Arcview Software 3.3. The analysis of the distribution of suspended sediment during ebb tide to word showed that the highest value was at 39 sampling point with the value of 66 mg/L.The lowest value was at the sampling points of 13 and 14 with the values of each at 2 mg/L. Meanwhile when recording toward lowtide thesampling point of 39 had also the highest value 85 mg/L and the lowest values were at the sampling points of 30, 38, 42, 43 and 44 with the value of 2mg/L each. Key word : Suspended solid, Mendol island, lowest tide